Implementasi SCM Pada UD. Sri Rezeki - Cindi Windiana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Technology and information are developing very rapidly at this time. Competition in the business world is very tight, forcing companies to do their best to improve their quality in all aspects. UD. Sri Rezeki is a factory trading business engaged in the cracker producer industry. Where every day this factory produces 400 kg of dough. Demand is increasing every day, of course, there is a need for sufficient raw material supplies for the production process of making Palembang curly crackers every day, in order to meet consumer demand on time. delays in the provision of raw materials for the production of crackers due to the absence of notification notifications regarding the stock of raw materials that have reached the minimum limit, and the ordering process to suppliers via telephone becomes ineffective and inefficient. In designing a web-based Supply Chain Management (SCM) application, it aims to manage supply chains from suppliers to retail at UD. Sri Rezeki, where the activities carried out can run well starting from ordering raw materials, the production process to the final activity, namely distribution to retail, can be managed properly.